PENERAPAN AZAS RUKUN, LARAS DAN PATUT DALAM PENYELESAIAN SENGKETA ADAT ( STUDI KASUS DI BANJAR ADAT AMBENGAN DENGAN BANJAR ADAT SEMANA KECAMATAN UBUD KABUPATEN GIANYAR PROVINSI BALI ) - Dharma Laksana, I Gusti Ngurah (VYAVAHARA DUTA, 2019)
Lands play an important role in our life. It becomes part of people’s life because lands are used to be the graveyards where the dead bodies are buried. The graveyard is also called as the ‘final resting place.’ As the role is very significant, especially in the life of customary village members in Bali, lands are often disputed among the members of one and other customary villages. The dispute becomes the object of many cases that ruins harmonious situation of native people in Bali. Take for example, the dispute that takes place in Banjar Adat Ambengan and Banjar Adat Semana Ubud District, Gianyar Regency and Bali Province. The problem to be solved is to investigate the causes of conflict as well as the implementation of land for peace, harmony, appropriateness and the parties involved in the settlement of the dispute. The investigation on the case that took place between the two customary villages was conducted through descriptive qualitative method supported by the case study approach. The finding showed that the dispute was settled by applying mediation method conducted through the meeting of the involved parties. It occurred several times with the principles of peace, harmony, and appropriateness to meet the society that live peacefully and harmoniously where people respect the existing customary law.